2018
DOI: 10.3390/s18030848
|View full text |Cite
|
Sign up to set email alerts
|

Design of Meter-Scale Antenna and Signal Detection System for Underground Magnetic Resonance Sounding in Mines

Abstract: Magnetic resonance sounding (MRS) is a novel geophysical method to detect groundwater directly. By applying this method to underground projects in mines and tunnels, warning information can be provided on water bodies that are hidden in front prior to excavation and thus reduce the risk of casualties and accidents. However, unlike its application to ground surfaces, the application of MRS to underground environments is constrained by the narrow space, quite weak MRS signal, and complex electromagnetic interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The receiver implements the MCU and CPLD as its core and is capable of functions such as serial-to-Ethernet conversion, receiver control timing generation and GPS synchronization. The MRS signal processing module includes a high-voltage relay, a tuning circuit, a preamplifier, high-pass and low-pass filters and a final amplifier [ 13 ]. The high-voltage relay prevents high voltage from damaging the receiver during the MRS transmission phase.…”
Section: Combined Mrs-tem Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The receiver implements the MCU and CPLD as its core and is capable of functions such as serial-to-Ethernet conversion, receiver control timing generation and GPS synchronization. The MRS signal processing module includes a high-voltage relay, a tuning circuit, a preamplifier, high-pass and low-pass filters and a final amplifier [ 13 ]. The high-voltage relay prevents high voltage from damaging the receiver during the MRS transmission phase.…”
Section: Combined Mrs-tem Instrumentmentioning
confidence: 99%
“…Commercial MRS instruments, such as GMR (Vista Clara, Santa Clara, CA, USA) and NUMIS (Iris, Orléans, France), are mainly employed for ground applications [ 11 , 12 ] and are often large in size and weight. In recent years, MRS instruments purposed for tunnels and mines have been substantially reduced in size and weight so that they can be used in narrow space environments [ 13 , 14 , 15 ]. Similarly, the most commonly-employed commercial TEM instruments available for underground measurements are the EM-47 (Geonics Limited, Mississauga, ON, Canada) and V8 (Phoenix Geophysics, Scarborough, ON, Canada); these instruments not only have the same problem in terms of size and weight, but they also have limited functionality.Considering this, [ 16 ] developed a combined MRS-TEM instrument based on the similarities between MRS and TEM instruments; consequently, test results demonstrated that their proposed instrument could effectively perform groundwater detection.…”
Section: Introductionmentioning
confidence: 99%
“…During orientation measurement in a tunnel, gyro data are not only affected by the constant and random drift errors of the sensor but also the external environmental factors, such as blasting, construction vibration, air draft-induced vibration of passing vehicles [6,7], magnetic field interference, and changes in temperature, humidity and air pressure [8,9]. These interference factors (especially physical vibration) cause abnormalities of the gyro signal, which contains significant non-stationary noise, leading to distortion of the orientation results [10].…”
Section: Introductionmentioning
confidence: 99%